An Evolutionary Approach to Political Leadership. (1st October 2016) - McDermott, Rose; Lopez, Anthony C.; Hatemi, Peter K.
ABSTRACT: We combine evolutionary and neurobiological models to provide a theoretically rigorous framework for understanding the origin of political leadership in democratic structures and how such qualities interact with institutional incentives and constraints. Evolutionary, behavioral-genetic, neuropsychological, and physiological studies have identified biological systems related to particular types of leadership behaviors as well as the emergence of leadership itself. These biological systems emerge during specific life stages and interact with a person's life history, influencing the environments one selects into and the perception of those experiences and subsequent reactions to them; these circumstances reinforce, suppress, and inspire various leadership characteristics. Our framework provides insight into the foundational basis of leadership qualities and explains why and how we observe variation in such traits. The evolutionary functions of leadership, including approaches to collective action problems, leader–follower dynamics, institutional and organizational environments, and leader attributes are discussed, and in so doing, we propose several novel questions that can be addressed from this perspective, which suggest new and fruitful lines of research in leadership studies.